Optimization of Productive Cash Waqf Funds on the Human Development Index - Isa Kholili (International Journal of Economic Research and Financial Accounting, 2023)
In this research, we will examine the optimization of cash waqf funds in order to increase the human development index of Ketawang Gondanglegi Village. The aim of this research is to find out the pattern of optimization (utilization) of waqf funds and to analyze the impact resulting from the utilization of cash waqf funds in increasing the human development index. This research was conducted in Ketawang Village, Gondanglegi District, Malang Regency with an implementation period of 8 months from May to December 2019. Data collection methods used interview, observation and documentation techniques while the data analysis tool used was Multiple Linear Regression. The research results show that cash waqf can have an impact on all areas including religious facilities, health, education and the economy if it is managed optimally and on target, namely in accordance with the proportion of needs or urgency of an area.